1987
DOI: 10.1104/pp.84.4.1421
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous NO3 in the Root as a Source of Substrate for Reduction in the Light

Abstract: ABSTRACIAn experiment was conducted to investigate the reduction of endogenOUS No3-, which had been taken up by plants in darkness, during the course of the subsequent light period. Vegetative, nonnodulated soybean plants (Glycine max [L]. Merrill, 'Ransom') were exposed to 1.0 millimolar I5N03-for 12 hours in darkness and then returned to a solution containing 1.0 millimolar 4NO3-for the 12 hours 'chase' period in the light. Another set of plants was exposed to 'I5NO3-during the light period to allow a dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
5
8
0
Order By: Relevance
“…The progressive increase of base excretion during the light period, and decrease in dark (NO3-fed plants, Figs. 5 and 6), is in accordance with the known kinetics of N03-reduction in soybean (26). During the light period, the inhibition of base excretion after girdling (85%) was as expected from the above estimate concerning the proportional shoot contribution of OH-.…”
Section: Discussionsupporting
confidence: 88%
“…The progressive increase of base excretion during the light period, and decrease in dark (NO3-fed plants, Figs. 5 and 6), is in accordance with the known kinetics of N03-reduction in soybean (26). During the light period, the inhibition of base excretion after girdling (85%) was as expected from the above estimate concerning the proportional shoot contribution of OH-.…”
Section: Discussionsupporting
confidence: 88%
“…Although soluble-'5N content was higher in the Na-treated plants, total soluble-N and nitrate-N content of the K-treated plants were about 126% and 182% of the Na-treated plants, respectively. Rufty et al (14) reported that "N was readily assimilated into insoluble macromolecules following 5NO3-reduction without staying in soluble reduced nitrogen in soybean plants. Accordingly, much more IN03-would be expected to remain in the K-treated plants than in the Na-treated plants.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that a larger proportion of the NO3-taken up by roots is translocated to the shoot in light than in darkness (22,24,29). The observation raises the possibility that xylem transport of NO3-is highly sensitive to a carbohydrate limitation.…”
mentioning
confidence: 89%
“…Utilization of carbohydrate reserves, the shoot being the main source, was most rapid during this time, and root respiration and NO3-uptake maintained at relatively high rates. A third phase was distinguishable over the next 12 h ofdarkness (h [24][25][26][27][28][29][30][31][32][33][34][35][36] Fig. 3A and 3B).…”
Section: Tissue Analysismentioning
confidence: 99%